3(4y-8)-(3y+9)=

Simple and best practice solution for 3(4y-8)-(3y+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4y-8)-(3y+9)= equation:


Simplifying
3(4y + -8) + -1(3y + 9) = 0

Reorder the terms:
3(-8 + 4y) + -1(3y + 9) = 0
(-8 * 3 + 4y * 3) + -1(3y + 9) = 0
(-24 + 12y) + -1(3y + 9) = 0

Reorder the terms:
-24 + 12y + -1(9 + 3y) = 0
-24 + 12y + (9 * -1 + 3y * -1) = 0
-24 + 12y + (-9 + -3y) = 0

Reorder the terms:
-24 + -9 + 12y + -3y = 0

Combine like terms: -24 + -9 = -33
-33 + 12y + -3y = 0

Combine like terms: 12y + -3y = 9y
-33 + 9y = 0

Solving
-33 + 9y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + 9y = 0 + 33

Combine like terms: -33 + 33 = 0
0 + 9y = 0 + 33
9y = 0 + 33

Combine like terms: 0 + 33 = 33
9y = 33

Divide each side by '9'.
y = 3.666666667

Simplifying
y = 3.666666667

See similar equations:

| 16x^4+39x^2-27=0 | | -3.5-1.5x=-13.5 | | 0.9x-18=1.5x-21 | | 11x-2y=58 | | a+(a+275000)=600000000 | | 2z^2+3=8z | | 2(x+1)+3x=x+5 | | 12(x-5)+5=0 | | 6x-11=x^2-6x+9 | | 4(3n-90)+6=190(6n+91) | | 6+3c=-1c-6 | | -3y-14=6y+13 | | x+105=6x | | x^2+7=97 | | 2(3x+5)=9x-3 | | Ab-cd=0(c) | | R-6=7-11-8 | | 4x-10=2(x+5) | | 2m^2+7m-4=0 | | 8x-11=29 | | 3x+3p-17=0 | | x+(x+18)=326 | | x+110=6x | | 5(x+5)=5(-8x+5)-x | | 5x+7=2x+22 | | 4x^4+31x^2-90=0 | | 3y+5.2=2y-5 | | y=4x^2-11 | | 6(x-8)+26=2(x-7) | | -3+16=6b-4-5b | | 3m+24=7m-16 | | 3.65-7.4x+1.12=21.76 |

Equations solver categories